Parents and Siblings as Role Models in Dealing With Digital Screen Media. Findings from A Media Fasting Intervention - Silke, Schwarz; Arndt, Büssing; Hanno, Krafft; Benjamin, Streit; Katja, Boehm; Till, Reckert; David, Martin (Journal of Women's Reproductive Health, 2024)
Parents' and siblings’ role model motivation and function could play an important role in positively influencing both their own media behavior and that of family members. To investigate whether parents and siblings consciously take on this role model function, their intentions were being evaluated with a standardized questionnaire before a 6-week media fasting intervention. 135 pairs of parents and 178 pairs of children were included. A major component of the parents' media fasting intention to media fast was to be a role model for their children. This was particularly related to the idea that media fasting has something cleansing about it, as well as the hope of becoming more attentive and calm as a family. These parents seem to want to strengthen family cohesion and climate and protect their children from excessive media consumption. Children who want to be role models for their parents also intend to have a positive influence within the family and want to be role models for their siblings. Regression analyses revealed several predictors of the parents' intent for role model function: the hope of becoming more attentive and calm as a family, the view that media fasting has something cleansing about it, and the perception that it is good for one's children to use less digital screen media, and, inversely, age (R2 =.35). The best predictors of the corresponding intention among the children were the desire to be a role model for their siblings, for the family to do more together again and, as for the parents, a younger age (R2=.57). The intentions of both groups are different, but the possibility of using less media is perceived as sensible. The role model function appears to be a relevant motivating and influencing factor regarding the conscious use of digital screen media and regulation of screen time. This should be taken into account when developing interventions.
Keywords: Digital screen media; Role models; Children; parents; Survey data